A Study on the Influence of Local Top Leaders' Corruption——An Empirical Analysis Based on the Municipal Party Committee Secretaries Sacked after the Eighteenth National Congress of the Communist Party of China - Liao Chongxu; Li Huoqiang; Zhou Dong (Contemporary Social Sciences, 2017)
Based on the cross-sectional data about the municipal Party committee secretaries sacked since the 18th CPC National Congress, this paper adopts a regression model to examine and assess the impact of local top Party leaders’ corruption. The study discovers that local heads’ integrity directly affects local political ecology they are in; that regions in the charge of corruptive heads suffer a higher degree of corruption; and that the tenure of corruptive local heads relates much to the degree of local corruption (i.e. the longer their tenure is, the more baneful influence they exert on the clean governance of local leaders and cadres). Consequently, it is imperative to establish and consolidate a power structure and a corresponding operating mechanism which enable effective mutual constraint and balance among decisionmaking power, executive power and supervision power. Only by doing so can China alleviate the negative impact of local heads’ corruption, effectively restrict and supervise local heads’ exercise of power, and maintain a well balance between “power delegation” and “power supervision”.